PENGUASAAN HAK PEMANFAATAN TANAH BADAN USAHA MILIK NEGARA (BUMN) OLEH ANAK PERUSAHAAN DALAM MELAKSANAKAN FUNGSI PELAYANAN PUBLIK STUDI KASUS : PT KERETA API INDONESIA (PERSERO) DENGAN PT INDONESIA COMNETS PLUS (ICON+) - Novia Irdasari, - (2019)
This research intend to find out the linkages and the responsibility of the land State-Owned Enterprises (SOEs) use rights by a subsidiary. This research uses a Normative Juridical as a method or library research which is conducted by reviewing the data based on primary source, secondary source, and tertiary sources based on a descriptive analytics. Indonesia is a state of law, as stated in Article 1 Paragraph (3) Undang-Undang Dasar (UUD) 1945, which requires legal rules to be attached to every activity, as seen through the economic sphere in Indonesia, there are many various business entities were formed which aimed to create a multiplier effect, as example State-Owned Enterprises (SOEs), that divided into several forms, such as, Perusahaan Perseroan, Perusahaan Perseroan Terbuka, Perusahaan Umum, each of them have a duty not only for get a benefit, but also required to complete the needs of people, as the states role in carrying out the efforts of public services, by the operational between the State Owned Enterprises (SOEs), we may see that there are also some of a variety conflict between SOEs, that started from the clash of interest and responsibilities, due to a lack of legal certainty regarding the limitations of rights and obligations in utilizing State-Owned land assets, that causes a loss to one of the parties who are considered to get the right first